2021
DOI: 10.1371/journal.pone.0258659
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and incidence of hepatitis A in Southeast Asia: A systematic review

Abstract: Background A previous review on hepatitis A virus (HAV) seroprevalence in 2005 categorized Southeast Asia as a low HAV endemicity region. In 2010, the World Health Organization modified this from low to low/medium endemicity, pointing out that these estimates were based on limited evidence. Since then, there has been no attempt to review HAV epidemiology from this region. We conducted a systematic review of literature to collect information on HAV incidence and seroprevalence in select countries in the Southea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In contrast, among unvaccinated adolescents, we observed the increased seroprevalence and antibody levels for HAV when compared with the other age groups, as well as the indifference in the antibody levels when compared with vaccinated individuals in the same age group. We hypothesized that some of the unvaccinated adolescents in this study might have already been exposed to HAV and/or have acquired an asymptomatic natural HAV infection during their adolescence 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, among unvaccinated adolescents, we observed the increased seroprevalence and antibody levels for HAV when compared with the other age groups, as well as the indifference in the antibody levels when compared with vaccinated individuals in the same age group. We hypothesized that some of the unvaccinated adolescents in this study might have already been exposed to HAV and/or have acquired an asymptomatic natural HAV infection during their adolescence 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of immunity to HAV is a significant concern for the suffering of symptomatic infection, fulminant hepatitis, and fatality among adults infected with HAV 36 . Also, since Chiang Mai province is bordered by Myanmar, where hepatitis A is still endemic 25 , there is a potential for disease outbreaks introduced by migrants crossing the border. HAV vaccine, either inactivated or live-attenuated, is well-tolerated, strongly immunogenic, and highly effective to prevent HAV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, HAV endemicity remains moderate to high in Southeast Asian countries (such as the Philippines, Taiwan, and Indonesia) 3,4 . It was reported that in the Philippines 62,63 in 2015 there was a steady increase in annual cases from 440 to 563, from 2016 and 2017 showed 443 and 462 cases per year, respectively. Nearly 50% of the affected people were between 16-30 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported in in 2021 6 that there was no published information on outbreaks in the Philippines, very limited information on seroprevalence for the last two decades, and that reporting up to date incidence data needs to be complemented with periodic seroprevalence surveys to fully capture the burden of HAV disease 62 .…”
Section: Introductionmentioning
confidence: 99%